GAMBARAN PEMERIKSAAN INPEKSI VISUAL ASETAT SEBAGAI DETEKSI LESI PRAKANKER SERVIKS DI HOTSPOT JALAN TUANKU TAMBUSAI KECAMATAN SUKAJADI PEKANBARU - Dhini Aiyulie Novri; Amru Sofian; Wiwit Ade Fidiawati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Cervical cancer is the third most frequent cancer in women in Indonesia.Indirect female sex worker are in high risk for having cervical cancer. WorldHealth Organization had recommended an alternative approach for developingcountries with down staging concept of cervical malignancy with visual inspectionwith acetic acid (VIA) to detect cervical precancerous lesion. This research wascarried out at hotspot Tuanku Tambusai Street, Pekanbaru aimed to describe thecharacteritics of respondent and to detect displastic cervical epithelial cells withVIA. The result showed from 31 indirect female sex worker, 52 % were diagnosedwith positive acetowhite appereance (positive VIA). Conclusion of the study thatdisplastic cervical epithelial cells of indirect female sex worker who has high riskfor having cervical cancer should be reffered for further follow up.Keywords: Visual inspection with acetic acid, Cervical cancer, Cervicalprecancerous lesion, Indirect female sex worker.